Trial to control infectious bursal disease virus using iron oxide chitosan nanocomposite in broiler chicken - Soad Nasef; Mervat Ayoub; Karim Selim; Dalia Elmasry (German Journal of Veterinary Research)
A severe outbreak of Infectious Bursal Disease (IBD) was recorded in 30 chicken flocks in different districts in Sharkia governorate during 2019, with high mortalities (up to 30%) and severe immunosuppression. Attempts to control IBD by an antiviral iron oxide chitosan nanocomposite was conducted. Eighty 21-day-old Baladi broiler chicks were divided into 4 groups. Group A; served as the negative control group, group B; was the challenge control group, group C; was the nanocomposite treatment group, and group D; received nanocomposite. The treatment contained 1 mg/ 100ml IC50 of iron oxide chitosan nanocomposite via the oral route administered for 3 days post-infection (PI). Results revealed that the iron oxide chitosan nanocomposite nano-size was 35.1±5nm with a stable state, zeta potentials16.8 ± 10.9, the PDI 0.91 and iron concentration in nanocomposite was 2625 mg/L. The virus shedding showed a significant decrease (P